Melatonin protects retinal pigment epithelium cells against ferroptosis in AMD via the PI3K/AKT/MDM2/P53 pathway - Wu, Ping; Zhao, Long; Du, Yong; Lu, Jing; He, Yuxia; Shu, Qinxin; Peng, Hui; Wang, Xing (Frontiers in Pharmacology, 2025)
IntroductionOxidative stress-prompted degeneration of the retinal pigment epithelium (RPE) notably contributes to the onset of age-related macular degeneration (AMD). However, the pathways leading to RPE deterioration and possible preventative strategies are not yet completely comprehended.MethodsFerroptosis was assayed through the evaluation of lipid peroxidation (C11-BODIPY and MDA), reactive oxygen species (ROS), transmission electron microscopy (TEM), iron content measurement, q-PCR, western blotting, and immunofluorescence. To assess the structure and retinal function of RPE in mice, ERG (electroretinography), OCT (optical coherence tomography), and H&E (hematoxylin and eosin) staining were employed. Network pharmacology methods were utilized to elucidate the potential mechanisms underlying melatonin's protective effects against ferroptosis in RPE cells in AMD. Genetic engineering techniques were applied to investigate the regulatory relationships among phosphatidylinositol 3-kinase (PI3K), protein kinase-B (AKT), murine double minute-2 (MDM2), protein 53 (P53), and solute carrier family 7 member 11 (SLC7A11). In vitro knockdown experiments of MDM2 were conducted to explore its regulatory role in ferroptosis within RPE cells.ResultsAβ1-40 can trigger ferroptosis in RPE cells. Melatonin can inhibit the oxidative stress and ferroptosis induced by Aβ1-40 in RPE cells. Melatonin exhibits a protective effect on Aβ1-40-induced AMD, significantly improving the structure of the mouse retina and RPE layer, and facilitating the restoration of visual function. Network pharmacology methods revealed that the potential targets of melatonin in AMD are closely related to ferroptosis, and indicated that the predominant pathways are significantly associated with the PI3K/AKT/MDM2/P53 signaling pathway. Knocking down the specific expression of MDM2 can significantly weaken the inhibitory effect of melatonin on oxidative stress and ferroptosis.DiscussionMelatonin can suppress cell death by ferroptosis in RPE via the PI3K/AKT/MDM2/P53 pathway, thereby preventing and decelerating the progression of AMD.